Looking for lost critical essays on the enigmatic series - Laist, Randy 1974- (McFarland & Company, 2011)
"This collection of fifteen essays by critics, academics, and philosophers examines the complete Lost series from a diverse but interconnected array of perspectives. Complementary and occasionally conflicting interpretations of the show's major themes are presented, including the role of time, fate and determinism, masculinity, parenthood and the threat of environmental apocalypse"--Provided by publisher